Vascular service provision during the COVID-19 pandemic worsened major amputation rates in socially deprived diabetic populations - AlMajali, Ali S.; Richards, Thomas; Yusuf, Syed Waquar; Telgenkamp, Bjorn (Frontiers in Endocrinology, 2024)
The Coronavirus Disease -2019 (COVID-19) pandemic significantly impacted healthcare service provision and put diabetic patients at increased risk of adverse health outcomes. We aimed to assess the impact of the COVID-19 pandemic on the incidence and demographic shift of major lower-limb amputation in diabetic patients. We performed a retrospective analysis of diabetic patient records undergoing major lower-limb amputation between 01/03/2019 and 01/03/2021 at the Royal Sussex County Hospital, the regional arterial hub for Sussex. Primary outcomes were amputation incidence rates and patient demographics compared between the prepandemic and pandemic cohorts. The incidence rate ratio of major lower-limb amputations shows a drop in amputations during the pandemic compared to pre-pandemic (IRR 0.82; 95% CI 0.57-1.18). Data suggests a shift in the social deprivation background of patients receiving amputations to disproportionately affect those in the more deprived half 50% of the population (p=0.038). Younger patients received more amputations during the pandemic compared to prepandemic levels (p=0.001). Results suggest that during the COVID-19 pandemic there was a paradoxical reduction in amputations compared to prepandemic levels. However, changes to the demographic makeup of patient's receiving amputations are alarming as younger, and more deprived patients have been disproportionately affected by the pandemic.